The Lost Identity : A Study from the Temporal Atomization of Social Networks - Baiget Pons, Jesús (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The human being is time. Temporality is our vital asset. The study of temporality appears to be inevitable if we want to fully understand any human reality. The aim is to expose the impact that the atomized conception of time typical of social networks such as TikTok or Instagram has had on young people in the construction of their individual identity. Starting from the bergsonian conception of time as vital continuity, we will see how the disintegration of temporal continuity and the absolutization of the instant have generated a disintegration of identity and a lack of meaning.